Lifestyle orientation of high versus low achievers in traditional school sports: an holistic analysis - Davies, Simeon (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1994)
One hundred and four subjects aged 16-18 years volunteered to participate in this study which sought to identify via an holistic model those factors that characterise the lifestyle orientations of high and low achievers (male and female) in traditional school sport. Subjects were evaluated with respect to their anthropometric, physiological, psychological and perceptual responses. The data were statistically analyzed by one way ANOVAS for significant differences in the following pairs; males and females, high and low achievers, Mhi (male high achievers) and Mlo (male low achievers), and Fhi (female high achievers) and Flo (female low achievers). Anthropometric results indicate that Fhi and Flo were significantly different in their stature, mass and body fat, while Mhi and Mlo show no significant differences. A greater disparity existed between VO, max of Fhi and Flo compared with Mhi and Mlo, along with trends in heart rate and RPE responses that were also more divergent. Psychological responses indicate that Fhi and Flo were significantly different in five of the seven sub-domains of CATPA, while Mhi and Mlo were only identifiable in one. In the PSPP Fhi and Flo were significantly different in all five subscales, while Mhi and Mlo in only two. This contrast in variability between the paired group analysis of Fhi and Flo as compared to Mhi and Mlo appears throughout the data.
Keywords: School sports; Achievement motivation